How Stocking Recreational Fisheries Works (and Sometimes Does not) - Nicholas Fisch; Diana Perry; Chelsey Crandall; Nick Trippel; Edward V. Camp (EDIS, 2022)
Stock enhancement or “stocking” is one of the oldest, most common, and most popular ways of improving recreational fisheries. Stocking is usually supposed to increase the number of fish available for anglers to catch. Unfortunately, stocking doesn’t always do this. The reasons why it may not always work as planned relate to some important concepts of fish ecology. This publication describes those ecological concepts and then also describes the three primary “outcomes” of stocking that anglers might observe. In the end, stocking can be very effective, but only if the stocked fish survive reasonably well and don’t decrease the population of wild fish.